2020
DOI: 10.1097/txd.0000000000000989
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal Dominant Polycystic Kidney Disease Is a Risk Factor for Posttransplantation Diabetes Mellitus: An Updated Systematic Review and Meta-analysis

Abstract: Background. Autosomal dominant polycystic kidney disease (ADPKD) is linked with risk for posttransplantation diabetes mellitus (PTDM), but this association has methodologic limitations like diagnostic criteria. The aim of this study was to use contemporary diagnostic criteria for PTDM and explore any risk association for kidney transplant recipients with ADPKD. Methods. We undertook a retrospective analysis of 1560 nondiabetic kidney transplant recipien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…An individualized approach to timing and need for nephrectomy based on patient's needs, preference, and surgical risk, would likely be the most optimal clinical practice 48 . Some studies 11,15,49,50 and meta-analyses 51,52 have showed increased risk of PTDM in PKD recipients, but this has not been a consistent finding 53,54 and most of these studies have small number of PKD patients. Amongst the 2 largest cohorts, however, one study has minimally increased risk of PTDM with PKD in an unadjusted analysis 15 while the other has none 54 In conclusion, renal allograft and patient survival is better in PKD than in other native kidney diseases post-kidney transplant.…”
Section: Discussionmentioning
confidence: 98%
“…An individualized approach to timing and need for nephrectomy based on patient's needs, preference, and surgical risk, would likely be the most optimal clinical practice 48 . Some studies 11,15,49,50 and meta-analyses 51,52 have showed increased risk of PTDM in PKD recipients, but this has not been a consistent finding 53,54 and most of these studies have small number of PKD patients. Amongst the 2 largest cohorts, however, one study has minimally increased risk of PTDM with PKD in an unadjusted analysis 15 while the other has none 54 In conclusion, renal allograft and patient survival is better in PKD than in other native kidney diseases post-kidney transplant.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, increased odds of developing PTDM among kidney transplant recipients with autosomal dominant polycystic kidney disease (ADPKD) have also been described [ 53 ], potentially related to polycystin-1 and polycystin-2 expression in organs outside of the kidney, such as the pancreas [ 54 ].…”
Section: Obesity and Ptdm After Kidney Transplantationmentioning
confidence: 99%
“…A large retrospective study of more than 25,000 transplant recipients showed that steroid-free immunosuppression was associated with a lower risk of PTDM occurrence compared to steroid-containing therapy. The cumulative incidence of PTDM within 3 years of transplantation was 12.3% and 17.7% for steroid-free therapy and steroid-containing therapy, respectively [ 53 ]. However, in a recent double-blind 5-year study comparing a group of patients who initially stopped corticosteroids with a group who reduced corticosteroids to 5 mg/day after 6 months, there was no difference seen in the rate of PTDM (35.9% in the group that discontinued corticosteroids, and 36.3% in the group that maintained 5 mg per day after 6 months) [ 56 ].…”
Section: Obesity and Ptdm After Kidney Transplantationmentioning
confidence: 99%
“…The mechanistic pathway for this association remains unclear but may be related to the direct viral-induced toxic effect on beta cells, induction of insulin resistance secondary to hepatic steatosis, and/or excess production of pro-inflammatory cytokines (83)(84)(85)(86)(87)(88)(89). Other less recognized risk factors for PTDM include the presence of autosomal dominant polycystic kidney disease and pre-and post-transplant hypomagnesemia, but these associations remain inconsistent and may be related to the residual effects of post-transplant confounding factors (90)(91)(92)(93)(94)(95). The failure of magnesium supplementation to improve insulin resistance and glucose metabolism in two small, randomized trials in kidney transplant recipients has challenged the potential causal relationship between hypomagnesemia and the development of PTDM (96,97).…”
Section: Risk Factorsmentioning
confidence: 99%